FORMATION OF THE COMPETITIVE STRATEGY OF THE AVIATION ENTERPRISE - TKACHENKO, Alla (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The current state of the Ukrainian economy requires solving many fundamental problems. Effective entry of the country into the international economic system requires urgent solution of a number of economic problems. Among many problems of the economic mechanism of Ukraine in the context of international integration, the issue of forming a competitive strategy of the air transport enterprise requires attention.A high level of competitiveness of an air transport enterprise should indicate the efficiency of its functioning, flexibility in adapting to changes in the operating environment, high quality of services and adaptation to changes in the operating environment, high quality of services and adequate pricing policy, positive consumer perception of the brand, the company's trademark, high level of staff qualification, etc. Therefore, it is important to theoretically substantiate the competitive strategy and improve the methodological recommendations for assessing the level of competitiveness of air transport enterprises.Competitiveness of an air transport enterprise in today's conditions is one of the defining characteristics of the efficiency of its economic activity and opportunities for further development. An important element of the system of ensuring the proper level of competitiveness of the air transport enterprise, the effective conduct of its economic activity is its assessment. As a result of a detailed study of the above approaches, an appropriate system of methods for assessing the competitiveness of an air transport enterprise should be formed. The advantages and disadvantages of the main groups of methods are also determined and the necessity of using a set of methods for a more complete assessment of the competitiveness of the enterprise is proved. For this purpose it is necessary to take into account the peculiarities of its economic activity.The modern stage of development of the Ukrainian economy puts forward qualitatively new requirements for the management of competitiveness of air transport enterprises.
Keywords: competitiveness; competitive strategy; competition; competitive advantages; competitive struggle